PENGARUH PENGGUNAAN MODEL KOOPERATIF TIPE THINK PAIR SHARE (TPS) DALAM PEMBELAJARAN PKn DI SEKOLAH DASAR - Reinita Reinita (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
This research aims at finding out the effects of using the Think Pair Share (TPS) type of the Cooperative Model toward 5th grade students’ learning outcomes of the civics subject at SDN 58 Lubuk Buaya Padang. The design of the research was Quasi Experiment. The population was all 5th grade students of the school. The samples were members of class VA and VB which consisted of 20 and 21 students. Based on the analysis of t-test, it was found that tcount > ttable (3,943 > 2,023). Thus, H1 is accepted. It means there is a significant use of the Think Pair Share (TPS) type to toward the 5th grade students’ learning outcomes of the civics subject.Keywords: the TPS learning model, learning outcomes